Juridical Analysis of the Corona Outbreak as a Reason for Force Majaure in Leasing - Riskamusdarniati Riskamusdarniati; Salmawati Salmawati; Muhammad Rinaldy Bima (Manunggal Halim Jaya, 2022)
Currently the world is shocked by an outbreak of a disease or virus that is very dangerous to humans and is a threat to global health. The name of the virus is Severe Acute Respiratory Syndrome Coronavirus 2 know as SARS-COV2 with the name Coronavirus Disease-2019 or COVID-19 or in Indonesia better known as Coronavirus. Coronavirus or corona virus was first discovered in China, to be precise in Hubei province, Wuhan city on December 8, 2019. Then on March 11, 2020 the World Health Organization declared COVID-19 a global pandemic after the virus began to spread to 114 countries. The spread of Covid-19 initially only exacerbated human health problems, but over time it cannot be denied that Covid-19 has also begun to affect the economic problems of a country. One of them is in the business world, in times like today the continuity of contracts and agreements has experienced some bottlenecks due to the pandemic. The existence of this condition can be used by the debtor as an excuse for renouncing a contract agreement that has been agreed upon with the creditor on the grounds of force or force majeure. Financial institutions engaged in the business world affected by the covid-19 outbreak are ADIRA Finance and BFI Finance.